Toponimi Candi di Trowulan: Kajian Antropolinguistik - Emilia Veti Rindi Febiani (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study used qualitative methods with an anthropolinguistic approach. Data were collected through observation, interviews, and documentation, and analyzed using Spradley's ethnographic analysis, which includes domain analysis, taxonomy, components, and cultural themes. The results indicate that temple toponymy in Trowulan is formed through three aspects: embodiment, society, and culture. The embodiment aspect is found in the names Gentong, Pertirtaan Tikus, Sumur Upas Kedaton, Kolam Segaran, and Wringin Lawang, which relate to environmental elements and physical characteristics of the site. The society aspect is represented by the name Minak Jinggo, which is associated with a figure preserved in the community's oral tradition. The culture aspect is reflected in the names Brahu and Bajang Ratu, which relate to history, oral tradition, beliefs, and cultural knowledge. The names of these temples in Trowulan also reflect cultural values regarding the relationship between humans and God, nature, and fellow humans. Furthermore, the names of sacred sites serve as a cultural identity for Majapahit, a marker of collective memory and ancestral heritage, and a medium for education and cultural tourism. This finding is utilized through the development of a digital audio guide accessible via QR code, containing information about the names, meanings, and cultural background of the temples. Thus, the names of the temples in Trowulan represent cultural knowledge that connects language, environment, society, history, and beliefs, while also providing an alternative medium for cultural preservation and cultural tourism development.
:: Finalisasi file repositori 31 Juli 2026_Kurnadi
Keywords: temple toponymy; anthropolinguistics; cultural values; Trowulan; cultural tourism